Analisis Makna, Fungsi, Dan Konteks pada Mantra Jaran Goyang - Heri Isnaini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Mantras are spelled out as part of the cultural values of a community. In the mantra text there are various concepts of the value of spirituality and religiosity. Mantras are also part of the means of asking for help and wishes in order to be granted by God. One of the mantras discussed in this study is the “Asihan Jaran Goyang” spell. This mantra aims to overcome the soul and soul of others to love and like the person who practices the mantra. In this study, “Asihan Jaran Goyang” was positioned into a text that was discussed based on the meaning, function and context of the narrative. The method used in this study is descriptive-qualitative by placing text analysis as the object of study. In addition, it also analyzes the context of mantra narration related to the practice that is a condition for obtaining power from the spell. The results showed that the structure of the “Asihan Jaran Goyang” mantra from the use of language, majas, and themes with isotopy analysis is related to the form of belief in God. Meanwhile, the function, context of narration and creation process describe the process of chanting mantras and practices that must be fulfilled by the mantra reciter, while functions indicate the functional usefulness of mantras by mantra reciters.